Schelmuffsky - Reuter, Christian (UNC Studies in the Germanic Languages and Literatures, 1962)
Rendered into English for the first time by Wayne Wonderley and provided with a critical introduction, this rollicking tale of baroque satire by Christian Reuter not only illuminates the mores and mentality of the time but forms a noteworthy link in the development of the European novel.